SOCIALIZATION OF HANDLING INCREASING BULLYING AMONG CHILDREN IN MENUR, SUKOLILO DISTRICT, SURABAYA - Susanto, Dany Agus; Utama, Yudhistira Prawira; Nurwachid, Achmad; Fauziah, Yessy Andriani (LPPM Univ. Ibn Khaldun Bogor, 2024)
Bullying is an increasingly common phenomenon, both in schools and in families. This is aggressive, repetitive, and deliberate behavior, aimed at hurting or dominating others emotionally, physically, or mentally. Bullying can occur in a variety of contexts, including at school, in the workplace, and online (cyberbullying). The causes of bullying vary, from unhealthy family conditions to mental disorders. The negative impacts of bullying are not only felt by the victims but also by the perpetrators, including emotional disorders and the risk of addiction. This phenomenon requires effective intervention to prevent bullying and protect individuals from legal and social impacts. The methods used include socialization about overcoming bullying in children, as well as discussions and questions and answers to ensure participants understand the importance of legal knowledge related to preventing, impacting, and overcoming bullying for both perpetrators and victims. This Community Service activity succeeded in raising awareness of the importance of overcoming bullying in children and protecting the rights of victims. Participants also understand that bullying can be carried out legally through the Child Protection Law and Article 1365 of the Civil Code.